Ипостаси художественного пространства: ностальгия и воображение (на примере повести Алексaндра Потемкина Кабала) - Korenowska, Lesława (Studia Rossica Posnaniensia, 2019)
Artistic space, presented in the story Kabala by A. Potyomkin, can be seen in various hypostases. The real, ethereal and ill-fated areas of the imagination of the main character connect with his opium dependence. Parfirchikov’s imagination is tightly connected with nostalgia, which manifests itself in the escape from the real world into the dreamed space of his inner world. Every character’s transformation from one space into another takes place after the dose of drug is taken by him.